Effects of 30 days of ketogenic diet on body composition, muscle strength, muscle area, metabolism, and performance in semi-professional soccer players. Issue 1 (16th September 2021) - Antonio Paoli, A.; Mancin, Laura; Caprio, Massimiliano; Monti, Elena; Narici, Marco V.; Cenci, Lorenzo; Piccini, Fabio; Pincella, Matteo; Grigoletto, Davide; Marcolin, Giuseppe
Abstract: Background: A ketogenic diet (KD) is a nutritional approach, usually adopted for weight loss, that restricts daily carbohydrates under 30 g/day. KD showed contradictory results on sport performance, whilst no data are available on team sports. We sought to investigate the influence of a KD on different parameters in semi-professional soccer players. Methods: Subjects were randomly assigned to a iso-protein (1.8 g/Kg body weight/day) ketogenic diet (KD) or western diet (WD) for 30 days. Body weight and body composition, resting energy expenditure (REE), respiratory exchange ratio (RER), cross sectional area (CSA) and isometric muscle strength of quadriceps, counter movement jump (CMJ) and yoyo intermittent recovery test time were measured. Results: There was a significantly higher decrease of body fat ( p  = 0.0359), visceral adipose tissue (VAT) ( p  = 0.0018), waist circumference ( p  = 0.0185) and extra-cellular water ( p  = 0.0060) in KD compared to WD group. Lean soft tissue, quadriceps muscle area, maximal strength and REE showed no changes in both groups. RER decreased significantly in KD ( p  = 0.0008). Yo-yo intermittent test improved significantly ( p  < 0.0001) in both groups without significant differences between groups. CMJ significantly improved ( p  = 0.0021) only in KD. Conclusions: This is the first study investigating the effects of a KD on semi-professional soccer players. In our study KD athletes lost fat mass without any detrimental effects on strength, power and muscle mass. When the goal is a rapid weight reduction in such athletes, the use of a KD should be taken into account. Trial registration: registered retrospectively on Clinical Trial registration number NCT04078971 .